The Effect Hydroquinone Extracted from Sonneratia caseolaris Fruit to Control Vibrio harveyi Artificial Infection on Tiger Shrimp, Penaeus monodon Fab. - Arifuddin, .; Sukenda, .; Dana, D. (Indonesian Society of Scientific Aquaculture (ISSA), 2004)
The role of hydroquinone extracted from Soneratia caseolaris fruit to control Vibrio harveyi infection on tiger prawn was carried out. In vitro experiment was conducted using disc diffusion and MIC minimum inhibitory concentration) methods to know the sensitivity of V. harveyi to hydroquinone. Two kinds of in vivo experiments were (1) hydroquinone was injected into shrimps muscle and a week later the shrimps were challenged with V. harveyi (2) the shrimps were challenged with V. harveyi and one day later hidroquinone was injected. Total count of live V. harveyi on the shrimps and survival rate were observed after challenge test. Hydroquinone showed antibacterial activity with MIC at 3000 ppm. Hydroquinone injected shrimp showed higher survival rate compared with control (100% vs 50%). Total count of V. harveyi from injected shrimp, either before or after challenged, decreased by 2,61xl04 cfu/g and l,61xl04 cfu/g, respectively. These findings indicated that crude hydroquinone have anti-bacterial effect to control V. harveyi infection. Key words: hydroquinone, Sonneratia caseolaris, Vibrio harveyi, Penaeus monodon ABSTRAK Telaah peran hidrokuinon yang diekstraksi dari buah Soneratia caseolaris untuk mengontrol infeksi Vibrio harveyi pada udang windu dilakukan. Percobaan in vitro dilakukan menggunakan metode difusi cakram dan MIC minimum inhibitory concentration) untuk mengetahui sensitivitas V. harveyi terhadap hidrokuinon. Percobaan in vivo dilakukan dengan dua cara (1) hidrokuinon disuntikkan pada otot udang dan seminggu kemudian udang diuji tantang dengan V. harveyi (2) udang ditantang terlebih dahulu dengan V. harveyi dan sehari kemudian hidrokuinon disuntikkan. Jumlah total bakteri V. harveyi hidup pada udang dan kelangsungan hidup udang diamati setelah uji tantang. Hidrokuinon menunjukkan aktivitas antibakteri dengan MIC 3000 ppm. Udang yang diinjeksi dengan hidrokuinon mempunyai kelangsungan hidup yang lebih tinggi dibandingkan kontrol (100% vs 50%). Jumlah total V. harveyi pada udang yang diinfeksi, baik sebelum maupun sesudah, masing-masing turun sampai 2,61 x 104 cfu/g dan 1,61 x 104 cfu/g. Hasil ini menunjukkan bahwa hidrokuinon mempunyai efek anti-bakterial untuk mengontrol infeksi V. harveyi. Kata kunci: hidrokuinon, Sonneratia caseolaris, Vibrio harveyi, Penaeus monodon",